Kegiatan Menggambar Ekspresi Sebagai Upaya Peningkatan Motorik Halus Anak PAUD: Studi Kasus di PAUD Nurul Kharomah Baratan Kecamatan Patrang Kabupaten Jember - Nurhayati, Umi; Burhani, Siti (Al-Riwayah : Jurnal Kependidikan, 2021)
Students' fine motor skills can be formed through drawing expressions. This drawing activity is very significant to be implemented in PAUD institutions, so many PAUD institutions implement these activities. One of the successful institutions is the PAUD Nurul Kharomah group B Baratan, Patrang District, Jember Regency. The focus of this research is how to improve children's fine motor skills through drawing expressions in PAUD Nurul Kharomah group B Baratan, Patrang District, Jember Regency, 2018-2019 Academic Year ?. To answer this focus, a qualitative research approach is used as a research method with the type of case study research. The results of his research indicate that efforts to improve children's fine motor skills through drawing expressions in PAUD Nurul Kharomah group B are carried out by the teacher explaining the various kinds of God's creations in the picture. Then, the teacher again invites the child to do different drawing activities from before, namely drawing expressions or freely. This activity runs well and optimally at the PAUD institution